Análisis económico del comportamiento adictivo: aplicación a las percepciones de riesgos asociados al consumo del tabaco - Portillo Pérez de Viñaspre, Fabiola (UNED. Universidad Nacional de Educación a Distancia (España) (España), 2001)
The economic models of addictive behaviour under uncertainty highlight the importance of the risk perceptions inherent to the consumption of harmful addictive goods, such as tobacco, in order to analyse the consumer choices. The subjective nature of the probabilities assigned by the individuals to these risks justifies the analysis of the formation of those perceptions, and on this matter, the Bayesian approach provides a useful theoretical development. In this context, the main objective of the study is to evaluate the influence of the information on the economic choices related to addictive goods, particularly tobacco. Two Spanish surveys provide the statistical data: one was applied in 1997 to a national sample of 2,500 respondents and the second one was implemented with a sample of 435 university students in 2000. From the national survey, we draw the main variables that affect the risk perceptions of the Spanish population -i.e. smoking, gender, age, and education-, which shows some distinctive characteristics that might explain, to some extent, the lower decrease in the prevalence of smoking in Spain against other developed countries. As for the analysis of the influence of the smoking risk perception on the consumer choice, the estimations resulting from the application of different econometrical methods indicate that this variable has a significant negative effect on the probability to become a smoker. Thus, an increase in the smoking risk perception would reduce its incidence among the Spanish population. These results are consistent with the hypothesis of rationality in the consumer choices and, moreover, with the conclusions of previous empirical studies. Likewise, we evaluate the potential impact of the new health warnings for tobacco packets recently imposed by the European Union. The results of the university survey suggest that the implementation of this anti-tobacco measure would have a statistically significant effect on the risk perception, estimated at a mean increase of 14.82%. Finally, we estimate the correspondence between the impact of this anti-tobacco policy based on information disclosure and the tax ones. The conclusion is that an increase in the tobacco price of 15.15%-24.83% would imply an equivalent increase in the risk perception.